Late Relapse of Diffuse Large B-Cell Lymphoma in a Patient with Minor Thalassemia: A Diagnostic Challenge - Stephanie Marisca; Jennifer Jesse Limanto (Fakultas Kedokteran Universitas Pelita Harapan, 2026)
Background: Diffuse large B-cell lymphoma (DLBCL) commonly responds to chemoimmunotherapy, and relapse risk usually decreases after prolonged remission. Thalassemia has been associated with increased risk of hematologic malignancy, although its relationship with late DLBCL relapse remains unclear. Case Description: A 68-year-old woman with minor thalassemia and a history of primary mediastinal B-cell lymphoma in complete remission for 15 years presented with fever and fatigue. Laboratory findings showed pancytopenia and elevated lactate dehydrogenase. FDG-PET/CT demonstrated increased uptake in the spleen and bone marrow. Bone marrow biopsy showed large B-lymphoid cells positive for CD20 and MUM1, establishing relapsed DLBCL with extranodal involvement. Complete remission was achieved after two cycles of R-COP chemotherapy, but the patient later died from severe infection, metabolic complications, and cardiomyopathy during the fourth cycle. Conclusions: Late relapse of DLBCL in patients with thalassemia is diagnostically challenging because cytopenia and systemic symptoms may overlap with hematologic complications. Long-term surveillance and prompt evaluation of new pancytopenia, splenomegaly, or systemic symptoms are essential in lymphoma survivors with thalassemia.